2012
DOI: 10.1111/j.1556-4029.2012.02068.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Content of THC and Other Major Cannabinoids in Drug‐Type Cannabis Cuttings and Seedlings During Growth of Plants*

Abstract: In Europe, authorities frequently ask forensic laboratories to analyze seized cannabis plants to prove that cultivation was illegal (drug type and not fiber type). This is generally done with mature and flowering plants. However, authorities are often confronted with very young specimens. The aim of our study was to evaluate when the chemotype of cannabis plantlets can be surely determined through analysis of eight major cannabinoids content during growth. Drug-type seedlings and cuttings were cultivated, samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
77
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 26 publications
(39 reference statements)
7
77
1
5
Order By: Relevance
“…Despite a lack of clinical evidence, patients suffering from HD may be seeking medical marijuana or acquiring it from other sources in an attempt to relieve some of the symptoms of their disease (Müller-Vahl et al, 1999;Meisel and Friedman, 2012;Koppel et al, 2014). Most medically available and tested illicit marijuana contains a high concentration of THC relative to other cannabinoids, such as CBD (De Backer et al, 2012). Here, we observed that THC reduced cellular function and viability in cells expressing mHtt whether THC was used alone or in a 1:1 combination with CBD.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a lack of clinical evidence, patients suffering from HD may be seeking medical marijuana or acquiring it from other sources in an attempt to relieve some of the symptoms of their disease (Müller-Vahl et al, 1999;Meisel and Friedman, 2012;Koppel et al, 2014). Most medically available and tested illicit marijuana contains a high concentration of THC relative to other cannabinoids, such as CBD (De Backer et al, 2012). Here, we observed that THC reduced cellular function and viability in cells expressing mHtt whether THC was used alone or in a 1:1 combination with CBD.…”
Section: Discussionmentioning
confidence: 99%
“…Also De Backer et al. and Pacifico et al. found exclusively THC‐predominant plants when investigating seized highly potent varieties from Belgium and Italy.…”
Section: Discussionmentioning
confidence: 97%
“…THC and the nonpsychoactive cannabidiol (CBD) are both enzymatic products from the same precursor, cannabigerol (CBG). In contrast to the absolute THC content, the relative CBD/THC ratio is fairly constant throughout the plant's life and relatively unaffected by external factors . Common Cannabis expresses three discrete chemical phenotypes (chemotypes): a THC‐predominant type (CBD/THC ratio 0.00–0.05), a CBD‐predominant type (CBD/THC ratio 15–25), and an intermediate phenotype (CBD/THC ratio 0.5–3).…”
mentioning
confidence: 99%
“…Research has found that CBG-A increases up to the twelfth week of cultivation (third week of flowering) and then decreases until the end of cultivation, while CBG increases all the way to the end of cultivation [44]. High CBG in seized cannabis plants may indicate that growers may be allowing their plants to mature before harvesting.…”
Section: Discussionmentioning
confidence: 99%